Information transfer and communication in surgery: a systematic review - Nagpal, Kamal; Vats, Amit; Lamb, Benjamin; Ashrafian, Hutan; Sevdalis, Nick; Vincent, Charles; Moorthy, Krishna (Annals of surgery, 2010)
We conducted a systematic review of published literature to gain a better understanding of interprofessional information transfer and communication (ITC) in hospital setting in the field of surgical and anesthetic care. Communication breakdowns are a common cause of surgical errors and adverse events. Medline, Embase, PsycINFO, Cochrane Database of Systematic Reviews, and hand search of articles bibliography. Of the 4027 citations identified through the initial electronic search and screened for possible inclusion, 110 articles were retained following title and abstract reviews. Of these, 38 were accepted for this review. Data were extracted from the studies about objectives, clinical domain, methodology including study design, sample population, tools for assessing communication, results, and limitations. Information transfer failures are common in surgical care and are distributed across the continuum of care. They not only lead to errors in care provision but also lead to patient harm. Most of the articles have focused on ITC process in different phases especially in operating room. None of the studies have looked at whole of the surgical care process. No standard tool has been developed to capture the ITC process in different teams and to evaluate the effect of various communication interventions. Uses of standardized communication through checklist, proformas, and technology innovations have improved the ITC process, with an effect on clinical and patient outcomes. ITC deficits adversely affect patient care. There is a need for standard measures to evaluate this process. Effective and standardized communication among healthcare professionals during the perioperative process facilitates surgical safety.